KEJAHATAN KORPORASI DALAM HUKUM PERBANKAN INDONESIA - Theodosiva Yovita (Perspektif, 2005)
Subjects involved in criminal law are people and corporation. In banking crime when a corporate involved the law enforcement is frequently less cared about. Therefore, it will be a need to do further study on how a banking law regulates the corporation crime in Indonesia. Corporation in Banking Law has a broader meaning than in Civil Law A form of corporation crime is raising fund from the community without any license from Central Bank of Indonesia, Bank Indonesia.